MongoDB for Read Intensive Cases Using YCSB (International Journal of Engineering and Computer Science, 2016)
With the emergence of cloud computing and continuously decreasing cost of the storage; it has become very easy to store unstructured data generated from the social media post, multimedia etc. To store unstructured data a new mechanism called NoSQL has evolved, which can store the data naturally and logically with lose restrictions on the database schema. This paper attempts to use NoSQL database system namely MongoDB for read intensive type cases, implementation scheme, and finally average run time compared of different cases with increase number of records and operations using YCSB.